Updates on p53: modulation of p53 degradation as a therapeutic approach - Dey, A (Nature Publishing Group, 2008)
The p53 pathway is aberrant in most human tumours with over 50% expressing mutant p53 proteins. The pathway is critically controlled by protein degradation. Here, we discuss the latest developments in the search for small molecules that can modulate p53 pathway protein stability and restore p53 activity for cancer therapy.